(untitled) (Paliativní medicína, 2023)
This case report describes the process of shared decision making in an adolescent patient with a progressive neuromuscular disease. The patient was referred for noninvasive ventilation (NIV) in sleep, but showed low compliance. Through the attending pulmonologist, a support care team was involved in order to explore patient’s preferences, wishes and concerns. A series of palliative care consultations allowed to clear his understanding of disease and prognosis, and led to a patient’s better understanding of the NIV purpose. Respecting the autonomy of the minor patient and eliciting his preferences subsequently led to improved quality of life and compliance with NIV.